Study on the Applicability of Sustainable Development Policies in Electricity Generation Systems in Colombia - Obregon, Luis; Valencia, Guillermo; Duarte, Jorge (International Journal of Energy Economics and Policy, 2019)
This study investigates the current situation of electricity generation from renewable energy sources in Colombia and the energy situation of the Colombian population. In general, it was demonstrated that Colombia has potential in renewable sources, mainly in solar energy, wind, and biomass. However, technical, economic and social barriers such as the lack of human capital, policies focusing on conventional technologies, high investment costs, as well as technological limitations due to the instability, intermittency and low efficiency inherent in renewable energy sources, have impeded their development. Despite the promotion of these renewable sources through Law 1715, greater commitments are needed to implement and improve energy policies, as well as investments in precise research on Colombia's energy potential and new existing technologies. For the technological limitations, this study proposes the use of energy storage systems, by means of battery systems or the use of biomasses such as chicken feather fibers and the peel of the oil palm for the production, storage and use of hydrogen as an energy gas. This with the aim of eliminating the instability and intermittency of renewable energy sources. Additionally, the advantages of thermoelectric devices are presented, which, coupled to photovoltaic cells allow increases of 2 to 10% in the efficiency of solar panels. In addition, the features of these devices allow you to generate electricity from the waste heat of virtually any process. This quality could increase in industrial sectors in Colombia such as the steel industry, the ceramics sector, the cement industry, and in the recovery of heat from the exhaust gases of diesel generators. The latter is used mainly in non-interconnected zones. This is intended to improve the efficiency of the processes, as well as the reduction of fuels in the case of diesel generators. Keywords: Renewable Energies, Energy Storage, Hydrogen, Thermoelectric Devices. JEL Classifications: O13, O38, Q42 DOI: https://doi.org/10.32479/ijeep.8375